Parents' reminiscing training in typically developing and 'at-risk' children: a review. Issue 1 (2nd January 2019) - Corsano, Paola; Guidotti, Laura
ABSTRACT: Reminiscing is a conversation between a child and caregiver about past events they have experienced together. In recent years, researchers have been interested in implementing training to improve the quality of parents' reminiscing styles, both in typically developing and 'at-risk' children and disadvantaged families. The review analysed studies on reminiscing training in order to provide support for their effectiveness, to identify gaps in the literature and to propose directions for future research. The review showed the effectiveness of reminiscing training for parents but highlighted the paucity of these studies, their focus on the mothers and the variability of the length of the training. Finally, the review emphasized the potential areas of reminiscing training in clinical and educational settings.